Kevin G. Grove, "Augustine on Memory, Oxford Studies in Historical Theology", Oxford University Press, New York 2021, pp. 266 - López-Arias, Fernando (Vox Patrum, 2023)
Review of the book Kevin G. Grove, "Augustine on Memory, Oxford Studies in Historical Theology", New York 2021.